SINERGITAS DALAM PEMBINAAN DAN PENATAAN PEDAGANG KAKI LIMA (PKL) DI KOTA BANDUNG - Zaenal Abidin As (Universitas Jenderal Ahmad Yani, 2019)
The existence of street vendors (PKL) in several big cities in Indonesia has caused a polemic which is still hot in discussion, where this relationship with spatial planning patterns in an area is causing problems. The problem of street vendors is not a new problem that only exists in Indonesia, even in Latin America and the Middle East itself experiencing the same thing, and the problem of the places where they sell sales and licensing is also a problem. The handling pattern by prioritizing synergy between the government and other parties in the handling process can answer problems related to the existence of street vendors in an area. Bandung city as a metropolitan city